Endoscopic Ultrasonography with Fine Needle Aspiration (EUS-FNA) for Esophageal Cancer Staging and Its Impact On Therapy - Azar, Riad R. (2006)
Background: To assess the utilization of EUS-FNA by thoracic surgeons and the perception of gastroenterologists who perform EUS-FNA for esophageal cancer staging and the impact of nodal involvement on therapeutic decisions, including surgical resection. Methods: A 15 question survey was distributed via email to gastroenterologists who perform EUS and thoracic surgeons who perform esophagectomies. This survey included questions related to clinical practice and communication between endoscopic ultrasonographers and thoracic surgeons.